Effects of the facial interface on inhalation and deposition of micrometer particles in calm air in a child airway model. (1st July 2014) - Xi, Jinxiang; Kim, JongWon; Si, Xiuhua A.; Su, Wei Chung; Zhou, Yue
Abstract: Context : How the facial interface affects particle inhalability and depositions within the airway is not well understood. Previous studies of inhalation dosimetry are limited to either inhalability or deposition, rather than the two studied in a systematic way. Objective : To systematically evaluate the effects of the facial interface on aerosol inhalability, nasal deposition and thoracic dose in a 5-year-old child airway model using a coupled imaging-computational fluid dynamics approach. Methods : A face–nose–throat model was developed from magnetic resonance imaging scans of a 5-year-old boy. Respiration airflows and particle transport were simulated with the low Reynolds number k-ω turbulence model and the Lagrangian tracking approach. Particles ranging from 1 to 70 µm were considered in a calm air. Results : Retaining the facial interface in the computational model induced substantial variations in flow dynamics, aerosol inhalability and thoracic doses. The nasal and thoracic deposition fractions were much lower with the facial interface due to the low inhalability into downward-facing nostrils and facial deposition losses. For a given inhalation rate of 10 L/min, including the facial interface reduced the thoracic dose by 5% for 2.5-µm particles and by 50% for 10 µm particles in the child model. Considering localized conditions, facial interface substantially increased depositions at the turbinate region and dorsal pharynx. Conclusion : This study highlighted the need to include facial interface in future numerical and in vitro studies. Findings of this study have practical implications in the design of aerosol samplers and interpretation of deposition data from studies without facial interfaces.